2013
DOI: 10.1186/1742-4755-10-21
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of contraceptive counseling at Srinagarind hospital, Thailand among women of reproductive age with systemic lupus erythematosus

Abstract: ObjectiveUnplanned pregnancy in women with SLE can have grave complications both for the child and the woman. We studied the prevalence of contraceptive counseling among women of reproductive age with SLE at a university hospital in Northeast Thailand.MethodsRecruited: 125 women with SLE, between 15 and 50 years, followed up at the Rheumatology Clinic. A questionnaire was administered and the results analyzed to identify the prevalence of contraceptive counseling.ResultsThe majority of women with SLE had had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…A listing of the studies to date examining contraception care among women with SLE is included in Supplementary Table , available on the Arthritis Care & Research website at http://onlinelibrary.wiley.com/doi/10.1002/acr.24346/abstract (8,11–22,28–33). These prior studies have revealed variable rates of contraception use among reproductive‐age women with SLE (22–85%) (11–21), and rates of HEC use among this population are even lower, in the range of 6–9% (19,22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A listing of the studies to date examining contraception care among women with SLE is included in Supplementary Table , available on the Arthritis Care & Research website at http://onlinelibrary.wiley.com/doi/10.1002/acr.24346/abstract (8,11–22,28–33). These prior studies have revealed variable rates of contraception use among reproductive‐age women with SLE (22–85%) (11–21), and rates of HEC use among this population are even lower, in the range of 6–9% (19,22).…”
Section: Discussionmentioning
confidence: 99%
“…A listing of the studies to date examining contraception care among women with SLE is included in Supplementary Table , available on the Arthritis Care & Research website at http://onlinelibrary.wiley.com/doi/10.1002/acr.24346/abstract (8,11–22,28–33). These prior studies have revealed variable rates of contraception use among reproductive‐age women with SLE (22–85%) (11–21), and rates of HEC use among this population are even lower, in the range of 6–9% (19,22). Additionally, studies examining contraceptive counseling in the outpatient setting among women with SLE have shown that 28–59% of patients at risk for pregnancy are not receiving counseling (13,18–20,28), including up to 46% of women using teratogens (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Cravioto et al discontinuation rate for different methods of contraception is significantly different; 35% in OCP, 55% in progestin-only pills (POP), and 29% in IUD ( 17 ). In a study in Thailand, among the SLE patients at risk for unintended pregnancy, only one-third used effective contraceptive methods and one-fifth did not have any background knowledge about SLE and pregnancy ( 10 ). Yazdany et al also observed that among 206 women with SLE, 86 were at risk for unplanned pregnancy, of whom 22% were inconsistent contraceptive users, 53% depended solely on barrier methods and IUDs were used by 13% ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, using the copper intrauterine device (IUD) is not believed to be associated with worsening disease activity or infection in women with SLE (5). Despite the crucial importance of contraception in women with SLE, it has been revealed that most of women who are at increased risk for unplanned pregnancy, do not receive appropriate contraceptive counseling (8)(9)(10). Therefore, these women will benefit from careful contraceptive counseling prior to pregnancy which can potentially lead to better maternalfetal outcomes.…”
Section: Introductionmentioning
confidence: 99%